Effects of Edaravone on Cardiac Damage in Valproic Acid Induced Toxicity - (:unkn) unknown (ASSOC CLINICAL SCIENTISTS, 2015)
Objectives. An increasing number of studies have pointed out the side effects of valproic acid (VPA), an antiepileptic drug used for the treatment of seizures in children and adults. The aim of this study is to evaluate whether VPA interferes with oxidative metabolism in the heart and whether edaravone, the novel free radical scavenger, ameliorates any such effects. Methods. Female rats were divided into four groups: intact control animals, VPA (0.5 g/kg/day), edaravone (30 mg/kg/day), and VPA+edaravone (0.5 g/kg/day+30 mg/kg/day) injected groups for seven days. On the 8th day the animals were sacrificed under ether anesthesia, and hearts were homogenized. Concentrations of malondialdehyde (MDA), sialic acid (SA), glutathione (GSH) and the activities of superoxide dismutase (SOD), catalase (CAT), glutathione - S- transferase (GST), glutathione peroxidase (GPx), myeloperoxidase (MPO), Na+K+ ATPase and tissue factor (TF) were evaluated in the homogenates. Key Findings. In the VPA group, increased MDA levels and decreased GPx activities indicated heart damage compared with the control group. On the other hand, edaravone treatment in the VPA group increased the activities of GST and SOD and decreased the activities of TF and ALP. Conclusions. Our study is the first to demonstrate the beneficial effects of edaravone on the impaired oxidant/antioxidant status of heart in VPA-induced toxicity.
Keywords: GLUTATHIONE-PEROXIDASE; EPILEPTIC CHILDREN; ALKALINE-PHOSPHATASE; ANTIEPILEPTIC DRUGS; LIPID-PEROXIDATION; RAT-HEART; ERYTHROCYTE GLUTATHIONE; SUPEROXIDE-DISMUTASE; ENZYMATIC DEFENSES; OXIDATIVE STRESS